Mental Health and Psychosocial Support Services (MHPSS) for Syrian Refugees in Lebanon: Towards a Public Health Approach Beyond Diagnostic Categories - Kerbage, Hala; Marranconi, Filippo (European Scientific Journal, ESJ, 2017)
Following the massive influx to Lebanon of Syrians fleeing armed conflict, the UNHCR and various NGOs, in collaboration with the Ministry of Public Health (MoPH), are providing Mental Health and Psychosocial Support Services (MHPSS) for Syrian refugees. However little is known about the functioning of these services and their implications in terms of defining the experience of suffering of refugees. Methods: we conducted a study of MHPSS services based on a review of documents published by UNHCR, MoPH, and relevant NGOs, as well as the analysis of the discourse of health care professionals/policymakers. 60 semi-structured interviews were conducted with informants from various organizations. The questions focused on their experience with the services, the main challenges encountered and their perceptions of the Syrian refugees and their problems. The list of organizations was taken from a service mapping by the MoPh. Findings: MHPSS interventions in Lebanon endorse the Inter Agency Standing Committee Guidelines that prioritize community-based interventions. Yet, in practice they promote individual-focused, clinical and short-term interventions rather than long term ones. Health care professionals perceive Syrian refugees as lacking awareness on mental health disorders and needing education in this regard; but most of them lack knowledge about the Syriansâ€™ patterns of social strengths and weaknesses and their perceived needs in terms of mental health. Conclusion: Based on our findings, we reflect on the relevance of â€œevidence-basedâ€ interventions in this particular setting and suggest recommendations for sustainable and culturally sensitive mental health interventions.